SPECIFICITIES AND CHALLENGES IN ADOLESCENT NUTRITION - Konatar, Ranka; Peličić, Damir; Maraš, Borko; Musić, Kenan; Miljanović, Goran (HEALTH CARE, 2024)
The aim of this review is to analyze the specificities of adolescent nutrition. Data were collected based on the search of the following databases: PubMed, SCOPUS and Google scholar. Bad eating habits of adolescents can lead to health problems such as delayed puberty, osteoporosis, reduction in final body height, hyperlipidemia, anemia, obesity, anorexia, bulimia, caries, and a balanced diet can prevent long term health problems such as cancers, atherosclerosis, stroke, osteoporosis, diabetes,  hypertension, etc. It is estimated that between 25% and 58% of overweight adolescents will become overweight adults, and between 24% and 90% of obese adolescents will become obese adults. In numerous works, a significant connection between skipping breakfast and a higher incidence of obesity has been observed. Girls (26%) skip breakfast significantly more often than boys (18%). Also, adolescents who skip breakfast eat food with high energy density significantly more often, which makes them hungrier and leads to overeating and obesity. Skipping breakfast can lead to risky behaviors, such as alcohol consumption, sedentary lifestyle, smoking, lower level of education and symptoms of depression. Physical inactivity is present in some countries as much as 50% of young people aged 11-25. It is necessary to educate adolescents about a healthy diet and the importance of physical activity, but it is even more important to start this education from an early age.
Keywords: adolescent, nutrition, physical activity, obesity, prevention